2008
DOI: 10.1073/pnas.0800001105
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of lithium-induced nephrogenic diabetes insipidus: Mechanisms for aquaporin 2 down-regulation and cellular proliferation

Abstract: Lithium is a commonly prescribed mood-stabilizing drug. However, chronic treatment with lithium induces numerous kidney-related side effects, such as dramatically reduced aquaporin 2 (AQP2) abundance, altered renal function, and structural changes. As a model system, inner medullary collecting ducts (IMCD) isolated from rats treated with lithium for either 1 or 2 weeks were subjected to differential 2D gel electrophoresis combined with mass spectrometry and bioinformatics analysis to identify (i) signaling pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
103
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 110 publications
(112 citation statements)
references
References 24 publications
4
103
0
2
Order By: Relevance
“…Although involvement of ␤-catenin in the embryonic development of the collecting duct has been well studied, [31][32][33] there is only indirect evidence regarding its relationship to vasopressin signaling in the mature collecting duct. 23 The amino acid sequence surrounding Ser-552 of ␤-catenin (…QRRTS 552 MGGT…) is consistent with a PKA motif. 27 Through 32 P labeling and site-directed mutagenesis, it has been shown previously that PKA can phosphorylate Ser-552.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Although involvement of ␤-catenin in the embryonic development of the collecting duct has been well studied, [31][32][33] there is only indirect evidence regarding its relationship to vasopressin signaling in the mature collecting duct. 23 The amino acid sequence surrounding Ser-552 of ␤-catenin (…QRRTS 552 MGGT…) is consistent with a PKA motif. 27 Through 32 P labeling and site-directed mutagenesis, it has been shown previously that PKA can phosphorylate Ser-552.…”
Section: Discussionmentioning
confidence: 89%
“…Because ␤-catenin has been proposed to play a role in regulation of aquaporin-2, 23 we investigated this response further using a phosphospecific antibody. Figure 5A shows an immunoblot performed on protein isolates from the same five pairs of animals used in our large-scale quantitation experiment.…”
Section: Regulation Of ␤-Catenin Phosphorylation By Ddavpmentioning
confidence: 99%
“…18 Prior studies showed that b-catenin phosphorylation at Ser-552 is regulated by vasopressin. [19][20][21] However, none of these studies addressed changes in subcellular localization.…”
Section: Cultured Mpkccd Cells (Recloned To Maximize Aqp2 Response Tomentioning
confidence: 99%
“…There is an emerging recognition of a role for b-catenin in vasopressin signaling in the renal collecting duct. [17][18][19][20][21] b-catenin is a multifunctional protein acting in at least three ways: (1) as a transcriptional coregulator, (2) as a component of the Wnt signaling network, and (3) as a component of adherens junctions. We also identified numerous proteins that putatively interact with b-catenin in collecting duct nuclei such as Cdh, Vcl, Scrib, Crebbp, Ep300, Tcf7l2, and Tax1bp3.…”
Section: B-catenin and Vasopressin Signalingmentioning
confidence: 99%
“…99 In skin, AQP3 is important for the phosphorylation of p38, ERK and JNK in keratinocyte, and less phosphorylation of p38 and JNK was observed in epidermis from AQP3-null mice which exhibit clearly impaired wound healing capacity compared to wild-type animals. 14 Further, the activation of GSK-3b, ERK, JNK, and p38 MAPK pathways has been associated with levels of AQP2 and proliferation in kidney collecting duct cells treated with lithium; 101,102 while the antiproliferative and anti-metastasis activity of anti-prostate cancer compounds such as Rg3 was associated with p38 MAPK-mediated downregulation of AQP1. 103 On the other hand, NF-kb seems to be the key transcription factor to which the actions of AQPs converge to produce a more proliferative phenotype.…”
Section: Cross-talk Between Transcription Factors Cytokines and Aqpsmentioning
confidence: 99%